VMware vSphere 5.5 cookbook : a task-oriented guide with over 150 practical recipes to install, configure, and manage VMware vSphere components /: a task-oriented guide with over 150 practical recipes to install, configure, and manage VMware vSphere components. (2015) - GB, Abhilash
No abstract available